The Design Management and Developing Design Brief A Critique on the Book The Design Brief book - Maryam Kahvand (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Today the design development and management of its process has become increasingly important. Based on the book review model, this article examines and critiques a book in the field of design development and planning with the aim of recognizing the features of design texts. “The Design Brief book” contains a collection of discussions, lectures and seminars by a well-known director and consultant of design strategies in the field of organizational identity management. The book content is written in two general sections: Design brief and design management. This descriptive-analytical study pays attention to the visual and technical characteristics of the book as well as the meaning of the content text. Considering the visual literacy of book’s audience, the color combination of the cover, lettering, and page layout of the book, needs to be revised and edited. Also, the lack of visualization and image tools leads to poor functioning and less attractiveness of the pages. The findings of the research in the study of the text indicate that the content of the book lacks an analytical approach to the subjects. The thematic relationship between the content of some chapters is not sufficiently coherent, although it does include some key points in the design of cryptographic design and design management.